Identification of the Anisotropic Elastic Parameters of NiCrAlY Coating by Combining Nanoindentation and Finite Element Method. (2nd June 2019) - Zhai, Jingyu; Chen, Yugang; Song, Xinyuan; Wu, Hongchun; Han, Qingkai
Abstract : For vibration damping, coatings are prepared on surface of the structures (substrates), which constitute the coating-substrate composite structures. Elastic parameters of the coating are indispensable for the vibration and damping analysis of the composite structure. Due to the small scale of coating thickness and elastic difference compared with the substrate, the identification results are inevitably influenced by the existence of substrate. Moreover, resulting from the preparation process, elastic properties of hard coating often exhibit anisotropic properties. All the above factors bring about the difficulties of accurate identification. In this study, a method for identifying anisotropic elastic parameters of hard coatings considering substrate effect is proposed, by combining nanoindentation and finite element analysis. Based on the identification results, finite element models are established to analyze the vibration characteristics of the coating-substrate composite structure, which verify the rationality of the anisotropic elastic parameters for vibration analysis. The studies in this paper are significant to more accurately identify the mechanical parameters for establishing the dynamic model. Moreover, they lay the foundation for further optimization design of hard coating damping.